Relation entre sentiment d'efficacité personnelle à entrer à l'université chez les étudiants de 1er cycle et stratégies de coping : construction et validation d'une échelle - Julien Masson; Laura Ratenet
enThe research presented in this article is about the development and validation of a scale and measurement of self-efficacy of students entering university (university SEP). This is an unprecedented tool that has been developed in several stages with a population of nearly 700 students enrolled in L1 in 13 different universities. The results of the exploratory factor analysis confirm a structure in three factors corresponding to the three potential difficulties identified by the students who enter the university (the management of the time, the creation of a social network and the emancipation of the glance of the others ) updated during semi-structured interviews. The prognostic validity of this self-efficacy is partialy confirmed by the correlations it has with other constructs conceptually linked (coping, stress).